Literature and reading under the light of intermedial and multimodality studies - Indrusiak, Elaine; Vieira, Miriam (Rizoma, 2023)
Professor Grzegorz Maziarczyk specialises in contemporary English and American literature and culture as well as transmedial narrative theory. His main research interests include textual materiality, intermediality, relations between literature and new media, multimodal storytelling, utopia and dystopia. He has been a recipient of fellowships and research grants from the University of Notre Dame, Katholieke Universiteit Leuven and European Society for the Study of English. He is the author of two monographs – The Narratee in Contemporary British Fiction (2005) and The Novel as Book: Textual Materiality in Contemporary Fiction in English (2013) – and the co-editor of five collections of essays, including (Im)perfection Subverted, Reloaded and Networked: Utopian Discourse across Media (2015) and Explorations of Consciousness in Contemporary Fiction (2017). He has published widely in edited collections and peer-reviewed journals, including Word & Image, Journal of Narrative Theory, Utopian Studies, Interfaces: Image, Texte, Language and Slavia amongst others. Since 2019 he has been Director of the Institute of Literary Studies at the John Paul II Catholic University of Lublin